Death in nineteenth-century Australia and New Zealand - Fraser, Lyndon (History compass, 2017)
The history of death, grief and remembrance is a significant aspect of the human past for it "takes us to the heart of any culture and sharpens our understanding of the meaning of our lives." Historians have really only begun to explore how people struggled to come to terms with mortality and shape its meanings in nineteenth-century Australia and New Zealand. Recent studies have refined our understanding of death and underlined its value for casting new light on aspects of the past. Scholars have also demonstrated how much we can learn about death and bereavement in the period by examining a wide range of sources—visual and material, as well as documentary. This essay highlights two key areas in the investigation of Australasian "deathways," a term that historians have used to capture the diversity of mortuary beliefs and practices, including ideas about the afterlife, relations with the dead, the preparation of corpses, funerary commerce, burial ceremonies, and rites of commemoration and remembrance. The first section surveys the scholarship surrounding indigenous practices before engaging with new work that places death at the centre of cross-cultural encounters on the colonial frontier. These recent histories reveal the importance of mortuary politics but they also raise thorny questions about sources and voice. The second section shifts attention to the great waves of migration to New Zealand and Australia during the nineteenth century. It considers debates about the Victorian "cult of death" and explores the key features of colonial ways of death.